Ultraviolet‐Light‐Induced Reversible and Stable Carrier Modulation in MoS2 Field‐Effect Transistors. (12th September 2014) - Singh, Arun Kumar; Andleeb, Shaista; Singh, Jai; Dung, Hoang Tien; Seo, Yongho; Eom, Jonghwa
<x xml:space="preserve">Abstract</x> The tuning of charge carrier concentrations in semiconductor is necessary in order to approach high performance of the electronic and optoelectronic devices. It is demonstrated that the charge‐carrier density of single‐layer (SL), bilayer (BL), and few‐layer (FL) MoS2 nanosheets can be finely and reversibly tuned with N2 and O2 gas in the presence of deep‐ultraviolet (DUV) light. After exposure to N2 gas in the presence of DUV light, the threshold voltages of SL, BL, and FL MoS2 field‐effect transistors (FETs) shift towards negative gate voltages. The exposure to N2 gas in the presence of DUV light notably improves the drain‐to‐source current, carrier density, and charge‐carrier mobility for SL, BL, and FL MoS2 FETs. Subsequently, the same devices are exposed to O2 gas in the presence of DUV light for different periods and the electrical characteristics are completely recovered after a certain time. The doping by using the combination of N2 and O2 gas with DUV light provides a stable, effective, and facile approach for improving the performance of MoS2 electronic devices.